Comparison of the rate constants of a bimolecular reaction using two methods - F. Shojaie (Arabian Journal of Chemistry, 2017)
There are different methods to calculate the rate constant of a bimolecular reaction. In this article are described two methods to calculate the rate constant and then these methods are compared using two-channel reaction. The rate constants for each reaction channel are calculated using Transition State Theory (TST) incorporating the Winger tunneling correction and the hindered rotor approximation. Furthermore, the rate constants for the dominant channel are calculated using general equation, which takes into account the rotational energy, is derived from Rice–Ramsperger–Kassel–Marcus (RRKM) theory, using the simplified version of the statistical adiabatic channel model theory. The vibrational mode analysis is used to elucidate the relationships of the reactant region (s = −∞), the saddle point (s = 0) and the product region (s = +∞).